Classic and new approaches to evaluate risk assessment for public health related to exposure to Halogenated Polycyclic Aromatic Hydrocarbons present in ludic waters - Morgado, Patricia I. (2017)
Risk assessment for public health related to exposure to Halogenated Polycyclic Aromatic Hydrocarbons present in ludic waters